Irregular terrain effect on radiowave propagation - Schejbal, Vladimir; Čermák, Dušan (Univerzita Pardubice, 2013)
An improved analysis of propagation over irregular terrain using physical optics approximation of vector problem is presented. It offers more reliable numerical simulations for low altitude propagation and diffraction field zone without any auxiliary procedures. Numerical simulations are compared with measurement results.
Vliv nerovného terénu na šíření radiových vln
Einfluss eines unebenen terrains auf die ausbreitung elektromagnetischer wellen